Action-Related Representations An Action-Based Approach to Grounded Cognition - Seuchter, Tim (Dissertations in Language and Cognition, 2020)
Theories of grounded cognition state that there is a meaningful connection between action and cognition. Although these claims are widely accepted, the nature and structure of this connection is far from clear and is still a matter of controversy. This book argues for a type of cognitive representation that essentially combines cognition and action, and which is foundational for higher-order cognitive capacities.